2014
DOI: 10.1186/cc13189
|View full text |Cite
|
Sign up to set email alerts
|

Low skeletal muscle area is a risk factor for mortality in mechanically ventilated critically ill patients

Abstract: IntroductionHigher body mass index (BMI) is associated with lower mortality in mechanically ventilated critically ill patients. However, it is yet unclear which body component is responsible for this relationship.MethodsThis retrospective analysis in 240 mechanically ventilated critically ill patients included adult patients in whom a computed tomography (CT) scan of the abdomen was made on clinical indication between 1 day before and 4 days after admission to the intensive care unit. CT scans were analyzed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
357
6
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(392 citation statements)
references
References 33 publications
17
357
6
12
Order By: Relevance
“…Wasting was evidenced by a reduction in rectus femoris cross-sectional area measured by ultrasonography and decreased muscle protein synthesis and increased muscle protein breakdown measured by muscle biopsy. Low skeletal muscle mass, estimated by the crosssectional area of muscle on abdominal CT scan, a previously validated measure of sarcopenia in older adults (77), is independently associated with in-hospital mortality in older trauma ICU patients and adults receiving mechanical ventilation (78,79). These findings are consistent with prior studies in community-dwelling older adults showing low muscle mass increases the risk for subsequent disability and mortality (80)(81)(82).…”
Section: Biological Correlates Of Frailty In Critically Ill Adultssupporting
confidence: 82%
“…Wasting was evidenced by a reduction in rectus femoris cross-sectional area measured by ultrasonography and decreased muscle protein synthesis and increased muscle protein breakdown measured by muscle biopsy. Low skeletal muscle mass, estimated by the crosssectional area of muscle on abdominal CT scan, a previously validated measure of sarcopenia in older adults (77), is independently associated with in-hospital mortality in older trauma ICU patients and adults receiving mechanical ventilation (78,79). These findings are consistent with prior studies in community-dwelling older adults showing low muscle mass increases the risk for subsequent disability and mortality (80)(81)(82).…”
Section: Biological Correlates Of Frailty In Critically Ill Adultssupporting
confidence: 82%
“…Diminished contractility and loss in muscle mass may occur independently; and thus, ICU-AW and muscle atrophy should not be construed to be synonymous or interchangeable [27]. A recent retrospective study demonstrated that muscle mass at ICU admission was an independent predictor of mortality [28]. Lower admission muscle mass was also associated with increased disability and higher frequency of discharge to a nursing home [28].…”
Section: Discussionmentioning
confidence: 97%
“…Our study provides further support for this "obesity paradox," with greater BMI increasing the likelihood of functional recovery among older adults after a critical illness. Notably, a recent study found that when muscle area was accounted for, BMI was no longer associated with mortality, whereas low skeletal muscle mass was a strong independent predictor of mortality (51). This suggests that skeletal muscle mass may be the factor that is truly responsible for functional recovery after a critical illness.…”
Section: Discussionmentioning
confidence: 99%